Analysis Thermal Behavior of a Locally Heated Solar Chimney - M, Aguilar-Castro, K.; V, Macias-Melo, E.; E, Torres-Aguilar, C. (International Journal of Membrane Science and Technology, 2023)
This paper presents the thermal behavior of a partially heated solar chimney under hot-humid climate conditions. The solar chimney (SCH) is 2 m high and 0.8 m wide and consists of an absorber plate and a translucent plate. The SCH allows a cavity thickness variation from 0 to 0.28 m, an inclination angle variation from 0 to 90º, and allows varying the amount of energy absorbed by the absorber plate and translucent plate. These plates were heated by resistors, simulating a solar irradiance range of 225 to 900 W/m2 (absorber plate) and from 12.15 to 50 W/m2 (translucent plate). Twelve tests were conducted with different configurations varying the power supplied to both plates, the thickness of the absorber plate cavity, and the 90º inclination angle. The variables measured were temperature, air velocity at the inlet, and heat flow on the side walls and rear wall. As a result, a maximum air renewal of 51.43 ACH was obtained, equivalent to the air changes used in a paint booth. The results show that the partially heated solar chimney can be used as a passive ventilation system for air renewal.